Potential evaluation of saline aquifers for the geological storage of carbon dioxide: A case study of saline aquifers in the Qian-5 member in northeastern Ordos Basin - Yan Li; Peng Li; Hong-jun Qu; Gui-wen Wang; Xiao-han Sun; Chang Ma; Tian-xing Yao (China Geology)
The well-developed coal electricity generation and coal chemical industries have led to huge carbon dioxide (CO2) emissions in the northeastern Ordos Basin. The geological storage of CO2 in saline aquifers is an effective backup way to achieve carbon neutrality. In this case, the potential of saline aquifers for CO2 storage serves as a critical basis for subsequent geological storage project. This study calculated the technical control capacities of CO2 of the saline aquifers in the fifth member of the Shiqianfeng Formation (the Qian-5 member) based on the statistical analysis of the logging and the drilling and core data from more than 200 wells in the northeastern Ordos Basin, as well as the sedimentary facies, formation lithology, and saline aquifer development patterns of the Qian-5 member. The results show that (1) the reservoirs of saline aquifers in the Qian-5 member, which comprise distributary channel sand bodies of deltaic plains, feature low porosities and permeabilities; (2) The study area hosts three NNE-directed saline aquifer zones, where saline aquifers generally have a single-layer thickness of 3–8 m and a cumulative thickness of 8–24 m; (3) The saline aquifers of the Qian-5 member have a total technical control capacity of CO2 of 119.25 × 106 t. With the largest scale and the highest technical control capacity (accounting for 61% of the total technical control capacity), the Jinjie-Yulin saline aquifer zone is an important prospect area for the geological storage of CO2 in the saline aquifers of the Qian-5 member in the study area.©2024 China Geology Editorial Office.